Peran Government Financial Dan Pertumbuhan Ekonomi Dalam Kesiapan Adopsi Paripurna International Public Sector Accounting Standards - Setu Setyawan; Ahmad Juanda; Lia Candra Inata (Universitas Muhammadiyah Malang, 2023)
Purpose: The objective of this research to assess and analyze the role of government finance and economic growth in influencing the readiness of plenary adoption of IPSAS. Methodology/approach: The sample in this study consisted of 198 research data from 33 provincial governments in Indonesia that sample criteria. The data of this study were analyzed using multiple regression analysis. Findings: The results of the study found that low level of government finance expected to role in the readiness of IPSAS plenary adoption. Meanwhile, the economic growth rate that is getting better or worse can influence the informer to disclose information in accordance with the elements of IPSAS. Practical implications: This research contributes to provincial governments and policymakers to better support the implementation of accrual-based IPSAS and is used guide for policymakers in determining whether plenary adoption is relevant so as to create value for public entities, especially public sector organizations. Originality/value: Regarding IPSAS, there has been no empirical research that analyzes the readiness of IPSAS plenary adoption with economic growth factors that play a role in IPSAS adoption readiness. So this needs to be done research that leads to the readiness of IPSAS adoption in full with factors that influence it.